SYNTHESIS AND CYTOTOXIC ACTIVITY OF CHALCONE DERIVATIVES ON HUMAN BREAST CANCER CELL LINES - Nuraini Harmastuti; Rina Herowati; Dyah Susilowati; Harno Dwi Pranowo; Sofia Mubarika (Universitas Gadjah Mada, 2012)
Chalcone, an α,β-unsaturated ketone, has been shown have many biological activities such as anticancer and antifungi. This research was conducted to synthesize the chalcone derivatives and to obtain their cytotoxic activity on human cervix cancer cell lines. Synthesis of chalcone and its derivatives, 4II-methylchalcone, 4II-methoxychalcone, and 3II,4II-dichlorochalcone was carried out using starting materials of benzaldehide and acetofenon, p-methylacetophenone, p-methoxyacetophenone, as well as m,p-dichloroacetophenone through Claisen Schmidt condensation catalized by NaOH in ethanol at 15 °C. The purity of synthesized compounds were analyzed by thin layer chromatography, melting range, and gas chromatography. Structure elucidations were conducted by UV spectrophotometer, IR spectrometer, 1H-NMR spectrometer, as well as mass spectrometer. Cytotoxic activities were determined by 3-[4,5-dimethylthiazol-2-yl]-2,5-diphenyltetrazolium bromide (MTT) microculture tetrazolium viability assay. The results showed that chalcone and derivatives compounds have been able to be synthesized and purified and had the same structure as a predicted structure. Chalcone had highest cytotoxic activity compared to that of its derivatives, with the IC50 values of chalcone, 4II-methylchalcone, 4II-methoxychalcone, and 3II,4II-dichlorochalcone were 9.49, 14.79, 11.48, and 24.26 µg/mL respectively. It was concluded that methyl, methoxy as well as chlorine substitution at 3 II and 4II position decrease the cytotoxic activity of chalcone.